Study of Allicin Extract Chelated with Some Heavy Metals (Cu2+, Co2+ and Pb2+) by Fluorescence Quenching Method and its Antioxidant Activity - Songsungkan, J.; Chanthai, S. (Asian Journal of Chemistry, 2013)
Organosulfurs, mainly allicin, generally found in natural garlic clove are known responsible for its antioxidant property. Extraction with 20 % (v/v) ethanol/deionized water followed by clean-up with C18-SPE of the allicin extract from fresh garlic clove was carried out and determined its antioxidant activity by 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 1,10-phenanthroline (Phen) methods. The complex formation between allicin and some heavy metal ions (Cu2+, Co2+ and Pb2+) was investigated by fluorescence quenching method. The experimental parameters were optimized including pH value, amount of the allicin extract, reaction time and concentration of nitric acid. The antioxidant activity of the allicin-metal complex was studied according to its labile chelating ability. It was found that their antioxidant activities of the allicin-metal complexes decreased (45 %) as compared with those of the allicin itself, considerably due to loss of free allicin in the extract, resulting in stability of the bound allicin complex under the optimum conditions. It is, therefore, implied that the organosulfurs play synergic functions of both as an antioxidant and a metal chelate.